2024
DOI: 10.3390/md22020093
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Nitrogen Availability: A Limiting Factor for Enhancing Fucoxanthin Productivity in Microalgae Cultivation

To Quyen Truong,
Yun Ji Park,
Jessica Winarto
et al.

Abstract: This study aimed to investigate the regulation of fucoxanthin (FX) biosynthesis under various nitrogen conditions to optimize FX productivity in Phaeodactylum tricornutum. Apart from light, nitrogen availability significantly affects the FX production of microalgae; however, the underlying mechanism remains unclear. In batch culture, P. tricornutum was cultivated with normal (NN, 0.882 mM sodium nitrate), limited (LN, 0.22 mM), and high (HN, 8.82 mM) initial nitrogen concentrations in f/2 medium. Microalgal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Two major FCP complexes can be isolated from Cyclotella meneghiniana as a central diatom [38,39]. It has been shown that the FCP complexes are sensitive to changes in environmental conditions and that the enhanced formation of FCP proteins has the potential to increase fucoxanthin biosynthesis [40,41]. Therefore, different environmental conditions may affect the production of fucoxanthin by Cyclotella meneghiniana.…”
Section: Introductionmentioning
confidence: 99%
“…Two major FCP complexes can be isolated from Cyclotella meneghiniana as a central diatom [38,39]. It has been shown that the FCP complexes are sensitive to changes in environmental conditions and that the enhanced formation of FCP proteins has the potential to increase fucoxanthin biosynthesis [40,41]. Therefore, different environmental conditions may affect the production of fucoxanthin by Cyclotella meneghiniana.…”
Section: Introductionmentioning
confidence: 99%